2008
DOI: 10.1007/s00384-008-0561-6
|View full text |Cite
|
Sign up to set email alerts
|

Referral patterns of patients with liver metastases due to colorectal cancer for resection

Abstract: This study highlights the advanced stage of colorectal cancer at presentation; in light of modern evidence-based, centre-oriented therapy of liver metastasis, we conclude that criteria of referral for resection should be based on the availability of treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…Other studies have demonstrated that survival rates can be further increased by both careful patient selection and centralizing liver surgery in dedicated centers. 26,27 In contrast to the association between hospital of diagnosis and the chance of undergoing a liver resection, no association was found between hospital of diagnosis and survival. This might indicate that hospitals use different criteria to select patients for liver resection.…”
Section: Discussioncontrasting
confidence: 68%
“…Other studies have demonstrated that survival rates can be further increased by both careful patient selection and centralizing liver surgery in dedicated centers. 26,27 In contrast to the association between hospital of diagnosis and the chance of undergoing a liver resection, no association was found between hospital of diagnosis and survival. This might indicate that hospitals use different criteria to select patients for liver resection.…”
Section: Discussioncontrasting
confidence: 68%
“…Our results revealed that the mean age at presentation for hepatic-only MCRC was 60.8 years, with a male preponderance. This is comparable to findings in the literature (Al-Sahaf et al, 2009;Ozturk et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, post-operative treatment and management of disease recurrence, was not consistent across study centers and limits direct comparisons. To date, studies of CRLM have evaluated time from presentation to definitive diagnosis [32], clinical characteristics and predictors of surgical referral [24, 33, 34] and time related to therapeutic decision making [6, 9, 16]. To our knowledge, ours is the first study to suggest that time from Dx-Rx is significantly associated with OS and propose that longer time intervals from Dx-Rx portend worse OS in patients with best risk resectable CRLM.…”
Section: Discussionmentioning
confidence: 99%